(untitled) (Swiss Medical Weekly, 2017)
Although we have detailed maps of epigenetic marks on DNA and chromatin for many cell types and disease states, the origin and significance of these patterns is incompletely understood. Deregulation of the epigenome is a frequent accompaniment to cancer, and it is therefore important that we learn how it contributes to tumour formation. Here it is proposed that the roles of DNA sequence signals as determinants of the epigenome have been underappreciated. Taking as a paradigm the part played by the dinucleotide CpG in regulating gene expression via its effects on the epigenome, it is suggested that factors recognising other short, frequent sequence motifs also recruit chromatin modifying enzymes in response to DNA sequence. A screen for factors of this kind promises to aid our understanding of the mechanisms by which gene activity is globally regulated.